2017
DOI: 10.3201/eid2301.160881
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cholera Vaccine Coverage during an Outbreak and Humanitarian Crisis, Iraq, 2015

Abstract: During November–December 2015, as part of the 2015 cholera outbreak response in Iraq, the Iraqi Ministry of Health targeted ≈255,000 displaced persons >1 year of age with 2 doses of oral cholera vaccine (OCV). All persons who received vaccines were living in selected refugee camps, internally displaced persons camps, and collective centers. We conducted a multistage cluster survey to obtain OCV coverage estimates in 10 governorates that were targeted during the campaign. In total, 1,226 household and 5,007 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 17 publications
1
42
0
1
Order By: Relevance
“…While cholera is vaccine-preventable, vaccinations are not routinely administered worldwide, including in Iraq, except for one round of oral cholera vaccination in 2015 (WHO, 2018). This one-time vaccination campaign successfully controlled the epidemic, as reported by the US Centers for Disease Control and Prevention (Lam et al, 2015). Such measures, along with immediate water treatment and case management, are priorities in times of outbreak (Lam et al, 2015).…”
Section: Other Who Surveillance Diseasesmentioning
confidence: 84%
“…While cholera is vaccine-preventable, vaccinations are not routinely administered worldwide, including in Iraq, except for one round of oral cholera vaccination in 2015 (WHO, 2018). This one-time vaccination campaign successfully controlled the epidemic, as reported by the US Centers for Disease Control and Prevention (Lam et al, 2015). Such measures, along with immediate water treatment and case management, are priorities in times of outbreak (Lam et al, 2015).…”
Section: Other Who Surveillance Diseasesmentioning
confidence: 84%
“…OCV used the mechanisms which had already been established to apply, import, and administer the vaccines rapidly, and this was accomplished in two weeks. In Iraq where an OCV campaign was carried out in response to a cholera outbreak and humanitarian crisis, the polio vaccine infrastructure was found to be a key success factor [33]. Through international networking, OCV Micro Planning used in Sierra Leon was adapted to suit the Borno context.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a review of published literature on post-OCV campaign vaccination coverage surveys and identified seven studies related to 24 two-dose campaigns conducted globally from 2003 through 2016 (Table S1) [15][16][17][18][19][20][21][22][23]. For each of the seven studies, we resampled two-dose (the standard vaccine regimen) coverage estimates 5000 times from a Gaussian distribution with a mean equal to the estimated coverage at the campaign site and the variance derived from the associated 95% confidence intervals; for studies with multiple locations, we first drew a single location randomly and then sampled from a Gaussian distribution of coverage estimates for that location.…”
Section: Campaign Coveragementioning
confidence: 99%
“…On the upper end, we assumed that individuals not directly protected by vaccine residing in grid cells with 30%, 50%, and 70% vaccination coverage experienced a respective 66%, 88%, and 97% reduction in cholera risk relative to a no vaccination scenario, according to a logistic model fit to published estimates ( Figure S4) (Longini et al 2007). Sensitivity parameters for vaccination coverage were taken from the 10th and 90th percentile resampled distribution of published coverage survey estimates from previous OCV campaigns ( Figure S1, Table S1) [15][16][17][18][19][20][21][22][23]. Sensitivity parameters for vaccine supply had, after 2019, either no growth or linear growth to 95 million doses in 2030; upper limit vaccine supplies may be achieved if new…”
Section: Sensitivity Analyses For Model Parametersmentioning
confidence: 99%